Detection and characterisation of Black Death burials by multi-proxy geophysical methods. (July 2015) - Dick, Henry C.; Pringle, Jamie K.; Sloane, Barney; Carver, Jay; Wisniewski, Kristopher D.; Haffenden, Austin; Porter, Stephen; Roberts, Daniel; Cassidy, Nigel J.
Abstract: The construction of the new Crossrail railway discovered 25 well preserved skeletons shallowly buried in Central London in 2013. Subsequent carbon dating and aDNA analysis confirmed the archaeological age and presence of the Yersinia pestis "Black Death" plague epidemic strain. Here we present the non-invasive multi-proxy geophysical survey of the adjacent Charterhouse Square, rapidly undertaken to detect any further burials and characterise the site. Historical records suggested the area was a burial ground for Black Death plague victims, before subsequent cemetery and urban land use. Following initial trial surveys, surveys imaged ∼200 isolated and similar-sized burials in the south-west of the site. There were also two contrasting burial orientations present at various depths which suggested a series of controlled phased burials. A well-defined eastern burial boundary, taking the form of a ditch and bank, was also discovered. Geophysical surveys also identified a subsequent complex site history with multiple-aged features. This study revises knowledge of Black Death aged-burials and provides important implications for successful geophysical burial detection with significant time- and space-limited site constraints. Graphical abstract: Highlights: Multiple skeletons discovered during Europe's largest construction project. Near-surface geophysical survey of Charterhouse Square revealed hundreds more. Burials were surprisingly isolated and not in mass burial pits. Burials were also phased and in different orientations. Radiocarbon dating and aDNA tooth analysis confirmed Black Death victims.